HIV and selected blood-borne and sexually transmitted infections in a predominantly Roma (Gypsy) neighbourhood in Budapest, Hungary: a rapid assessment - Gyarmathy, V Anna; Ujhelyi, Eszter; Neaigus, Alan (Central European journal of public health, 2008)
We assessed the prevalence of HIV and selected blood-borne and sexually transmitted infections among a convenience sample of 64 residents of Dzsumbuj, a predominantly Roma (Gypsy) neighbourhood in Budapest, Hungary. No cases of HIV were detected, while the prevalence of hepatitis B infection (anti-HBc) was 27% and syphilis prevalence was 2%. Romas (n = 50) were significantly more likely than non-Romas (n = 14) to have HAV antibodies (80% vs. 43%) and less likely to be HBV immunized (anti-HBs only; 6% vs. 29%). Current drug injectors (n = 13) were more likely than non-injectors (n = 51) to have antibodies against HAV (85% vs. 69%) and HCV (85% vs. 8%). While HIV has not been introduced in this population, risk conditions for a potentially explosive HIV epidemic are present. Health care policies should focus on expanding coverage for HAV and HBV immunizations, and access to HIV preventive services needs to be extended to marginalized, mostly minority populations, such as the Roma in Europe.
Keywords: Female; poruchy spojené s užíváním psychoaktivních látek; Hepatitis B; Hungary; mužské pohlaví; surveillance populace; mladý dospělý; Humans; Prevalence; hepatitida B; dospělí; Romové; lidé; Maďarsko; sexuálně přenosné nemoci; HIV infekce; Roma; ženské pohlaví; HIV Infections; Young Adult; Substance-Related Disorders; prevalence; Adult; Male; Sexually Transmitted Diseases; Population Surveillance